Determinants of capital structure adjustment speed in the Malaysia property industry - Sharala Nair, Achudan (2020)
The main focus of this study is to examine the firm’s size, firm’s growth opportunity, firm’s profitability, corporate taxation, corruption, and political stability and the absence of violence impacts on capital structure adjustment speed in the Malaysia property industry. This research is conducted on the 70 listed property companies in Malaysia and the data was collected from the Bursa Malaysia website and the World Bank website using a data stream. Findings of the research revealed that only two (2) out of six variables having a significant relationship with the firm’s capital structure adjustment speed, which are the firm’s growth opportunity and firm’s profitability. A firm with a higher growth opportunity will need more funds to finance their growing investment opportunity as internally generated funds usually not enough to meet the growing opportunity. Higher growth firms will frequently visit the financial market to meet their financing requirements. On the other hand, a profitable firm will prefer to use external sources of funds rather than internal funding to benefits from the tax deduction of interest expense on debt financing.